Micropropagation of guava (Psidium guajava) seedlings, a plant with interest in cool subtropics, using an innovative BB culture medium - Thiresia-Teresa Tzatzani; Ioanna Michail; Anastasia Boutsika; Eirini Sarrou; Ioannis Ganopoulos (Biotechnology & Biotechnological Equipment)
Psidium guajava is a new crop cultivated in Greece, with a potential pharmaceutical and ornamental uses. An efficient and reliable protocol for in vitro clonal propagation of P. guajava from seeds was used. Five different media were examined. Shoot proliferation succeeded on a new basal medium (BB) supplemented with a modified vitamin solution (vit BB), without plant growth regulators. In addition, shoots on media supplemented with BB vitamin solution performed better than in Murashige and Scoog (MS) and Woody Plant (WP) media. When BB medium was used, the greatest shoot number resulted in 4 mg L−1 6-benzyladenine (BA) with a score of 2.8. Regenerated single shoots were rooted in the BB medium, supplemented with 0.1 ΝΑΑ (mg L−1) and producing 2.2 roots of 4.6 cm, along with 3.1 cm of adventitious shoots. Acclimatization was accomplished in three phases, using peat-moss, vermiculite and perlite (1:1:1), with a total survival of 83.3%. To examine the genetic diversity of the plant material, Inter Simple Sequence Repeat (ISSR) and Start Codon Targeted (SCoT) molecular markers were used. The results indicated a low diversity, along with high percentage of polymorphism for both ISSR and SCoT analyzes.